Measuring the world of (vocational) education - the Report on Vocational Education and Training and the BIBB Data Report - Friedrich, Michael [Verfasser]; Krekel, Elisabeth M. [Verfasser] (My University, 2011)
"Germany’s National Education Report, first published in 2006, is the first comprehensive report covering all areas of education. However, ongoing reporting in the field of vocational education and training (VET) has been in place for more than 30 years in the form of the Report on Vocational Education and Training published by the Federal Ministry of Education and Research (BMBF). The Federal Institute for Vocational Education and Training (BIBB) has thus far been involved with the preparation of this report within the scope of ist statutory functions. Following a realignment of the Report on Vocational Education and Training in 2009, BIBB now issues the Data Report, a new standard work on VET. The Data Report is based on selected indicators and depicts the main developments within initial and continuing vocational education and training within an international context. In addition, different focal topics are dealt with each year." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.1.1 Ausbildungsstellenmarkt; Benchmarking; Berufsbildungsbericht; Indikatoren; Angebot-Nachfrage-Relation